Establishment of a fluorescent reporter of RNA-polymerase II activity to identify dormant cells - Rasmus Freter (Nature Portfolio, 2021)
The identification and characterisation of dormant cells is currently difficult. Here the authors report Optical Stem Cell Activity Reporter (OSCAR) to assess RNA polymerase II activity and identify dormant cell populations in intestinal epithelial cells in vivo.